Associations Between Body Composition, Leptin, and Vitamin D Varied by the Body Fat Percentage in Adolescents - Khwanchuea, Rapheeporn; Punsawad, Chuchard (Frontiers in Endocrinology, 2022)
Background: Serum leptin levels reflects one’s degree of obesity and can affect vitamin D levels. The relationship between body fat, leptin, and 25-hydroxyvitamin D (25(OH)D) has not been extensively studied in adolescents. This study aimed to investigate the correlations between body composition and leptin and 25(OH)D levels in boys and girls. Methods: Participants aged 12–14 years (n = 205) were grouped according to sex. After body composition was recorded using bioelectrical impedance analysis, they were classified into three groups according to body fat percentage (%BF) ( 30,  30 and < 40, and  40). Serum leptin and 25(OH)D levels were measured using the enzyme-linked immunosorbent assay (ELISA). Correlations between all variables were analyzed according to sex and the percentage of BF groups. Results: Boys and girls with %BF  30 showed no difference in body mass index (BMI), %BF, and leptin and 25(OH)D, while other variables of body composition were more common in boys than in girls. The %BF, body fat mass (BFM), and 25(OH)D of both sexes with %BF  30, and leptin levels of boys with %BF  40 increased with an increase in %BF. A negative correlation between leptin and 25(OH)D levels was found in boys with %BF < 40 and girls with %BF < 30. In the %BF  30 and < 40 groups, there were negative correlations between leptin, BFM, free fat mass, and muscle mass (MM); between leptin, 25(OH)D, and height in boys; and between 25(OH)D, body weight, BMI, and MM in girls. Conclusion: A negative correlation between leptin and 25(OH)D levels varied according to sex, while for body composition, it was evident at 30 and 40% BF.